DIRECTIVE SPEECH ACT IN LOUISA MAY ALCOTT’S NOVEL LITTLE MEN - Fitriyah Fitriyah (JOURNAL OF LANGUAGE, 2022)
Speech acts are central entities in pragmatics. The research aims to describe kinds and functions of directive speech act in the novel Little Men by Louisa May Alcott. This research uses descriptive research. The steps of data analysis were carried out by; 1) collecting data (reading novels repeatedly and marking data including directive speech acts), (2) reducing data (identifying and classifying the types and functions of directive speech acts, 3) presenting data, 4) drawing conclusions and verifying data. The result of this research shows that there are 301 directive speech acts. There are seven kinds of directive speech acts that are found in this novel. Those are questioning (41,8%), ordering (24,5%), commanding (7,3%), advising (5,3%), begging (6,6%), inviting (4,9%), and prohibition (8,3%). With this research, it is hoped that the reader will be able to understand the meaning of speech through the actions of the speaker in the novel Little Men.